AGAMA DALAM GENGGAMAN, MORAL DALAM KEGAMANGAN: TANTANGAN PENDIDIKAN HINDU DI ERA DISRUPSI DIGITAL - Ida Bagus Ketut Tresna Manuaba (Yayasan Pendidikan Literasi Borneo, 2026)
This study aims to analyze the challenges of Hindu Religious Education in the era of digital disruption, particularly related to changes in religiosity and the morality of Hindu youth. The research employed a qualitative approach with a descriptive-critical design. Data were collected through observation, interviews, documentation, and literature studies. The findings show that the development of digital technology has changed the way Hindu youth understand and practice religion through social media and virtual spaces. Digital media has become a new medium for gaining spiritual knowledge and expressing religious identity. However, this condition has also led to symbolic religiosity and moral uncertainty due to visual culture, social imaging, and weak internalization of moral values. Hindu Religious Education faces challenges because learning methods remain conventional and religious digital literacy is still low. This study found that Hindu values such as dharma, tat twam asi, ahimsa, and susila remain relevant in building digital ethics among young people. Therefore, Hindu Religious Education needs to be developed in a contextual, humanistic, and digital literacy-based manner in order to shape a religious and morally grounded young generation in the digital era.